Informing or persuading travellers: the language of airlines advertisements - María Luisa BLANCO GÓMEZ (Ediciones Universidad de Salamanca, 2012)
In the advertising world choosing the right kind of language can lead us to becoming a successful company or not, since the choice of different kinds of words and different structures is crucial when trying to persuade people. In this paper many variables will be taken into account, from the characteristics of advertising English to those specific from Tourism English bearing also in mind the globalized world around us and consumer perception, which is an essential element in the advertising process, analyzing discursive and linguistic features. In this study we will focus on the most frequent structures in the advertisements published in the Time Magazine about some international airline companies and will examine whether the language used can achieve a persuasive effect on the potential customer or not.